2018
DOI: 10.1097/htr.0000000000000344
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Posttraumatic Stress Disorder and Traumatic Brain Injury: Generalization of Prolonged-Exposure PTSD Treatment Outcomes to Postconcussive Symptoms, Cognition, and Self-Efficacy in Veterans and Active Duty Service Members

Abstract: PE treatment-related improvements for participants with comorbid PTSD and TBI generalize from PTSD outcomes to PCS and other TBI-related outcomes. Positive outcomes were independent of TBI severity, treatment setting, or Veteran status, but dependent upon PE treatment completion and lower levels of VA service-connected disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…This improvement was evident across the different sources of information (i.e., self-report, parent report, clinician ratings, objective tests), thus supporting the validity of our findings. As reported in previous studies of adults (Sripada et al, 2013;Wolf et al, 2018), treatment outcomes were not related to mTBI diagnosis, suggesting that children with comorbid PTSD and mTBI may benefit from trauma-focused interventions and do not necessarily need a specialized and more complex intervention.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This improvement was evident across the different sources of information (i.e., self-report, parent report, clinician ratings, objective tests), thus supporting the validity of our findings. As reported in previous studies of adults (Sripada et al, 2013;Wolf et al, 2018), treatment outcomes were not related to mTBI diagnosis, suggesting that children with comorbid PTSD and mTBI may benefit from trauma-focused interventions and do not necessarily need a specialized and more complex intervention.…”
Section: Discussionsupporting
confidence: 64%
“…Typically, evidencebased treatments for mTBI and PTSD have been examined independently, and research that has examined psychotherapeutic interventions for PTSD in patients with a history of mTBI is limited (Davis, Walker, Chard, Parkinson, & Houston 2013;Tanev et al, 2014). The findings of a few studies have suggested that cognitive behavioral therapy (CBT) may be effective in treating PTSD following mTBI in adults (Bryant, Moulds, Guthrie, & Nixon, 2003;Soo & Tate, 2007;Sripada et al, 2013;Wolf et al, 2018). However, to the best of our knowledge, no studies to date have addressed this issue in children.…”
mentioning
confidence: 99%
“…The most commonly reported facilitator was compensatory strategies for cognitive challenges. Thirteen of the included studies specifically noted accommodations in treatment to address cognitive challenges associated with TBI, four studies listed these as accommodations as facilitators [ 65 , 67 , 101 , 105 ], while an additional nine studies simply noted that the accommodations were put in place to support participants [ 54 , 58 60 , 66 , 72 , 79 , 84 , 92 ]. The accommodations reported were aimed at overcoming barriers in participation, improving treatment adherence, and supporting task completion and ranged from appointment reminders [ 65 ], to psychoeducation [ 101 ], to adjusting the frequency and duration of sessions [ 67 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from case studies, which predominantly comprised participants of a single sex or gender, none of the articles in this review reported sex- or gender-stratified data. Furthermore, two studies reported findings on men and women but were described as ‘sex’ [ 55 , 56 ] while 12 studies reported findings on males and females but were described as ‘gender’ [ 69 , 74 76 , 85 , 86 , 92 , 95 , 98 , 103 105 ]. Clear reporting of sex and gender data are needed to inform gender transformative integrated care.…”
Section: Discussionmentioning
confidence: 99%
“…There is a dearth of research, however, on self‐efficacy and coping style in the context of comorbid mTBI history and PTSD, and no known studies have examined these constructs within combat‐exposed Veterans with this comorbidity. Notably, however, both self‐efficacy and coping style have been shown to be alterable, or malleable, traits (Anson & Ponsford, 2006; Boden et al, 2014; Douglas et al, 2019; Tyrrell et al, 2019; Wolf et al, 2018) and thus may be important treatment targets.…”
Section: Introductionmentioning
confidence: 99%